Polyarthrite Rhumatoïde en Consultation Rhumatologique à Maradi, Niger - Salissou, Garba Mahaman; Kaba, Condé; Adamou, Garba Idé; Alassane, Seydou; Fanata, Moussa (European Scientific Journal, ESJ, 2019)
Rheumatoid arthritis (RA) is the most common auto-immune disease. Rarely described in Niger, we reported its epidemiological, clinical, paraclinical, therapeutic, and evolutionary aspects in hospitals environments. In order to analyze these aspects in detail, a prospective study has been realized over a period of one (1) year in the Rheumatology Department of the Regional Hospital Center of Maradi. We have included all RA cases in accordance with the ACR/EULAR classification criteria of 2010. The data was entered and analyzed on SPSS 20.0 software. After collecting and studying 32 AR observations from among 846 rheumatologic consultations, the results have demonstrated different points: the average patient’s age is 38,9 years, the delay for the diagnosis was 6 years, and in some cases extraarticular manifestations have been observed. The results show that the inflammatory syndrome was constant and that the treatment remains classic with non-pharmacologic means, analgesics, NSAID (non-steroidal antiinflammatory agent), infiltrations and DMARDs (disease-modifying anti- rheumatic drug). The evolution is positive in all the cases. Thanksto thisstudy it is possible to affirm that rheumatoid arthritis is a reality in Niger and it has been better described. The diagnosis is late, the articular and systemic manifestations are the same as in Caucasians, but the autoimmunity seems less. The disease is very active, altering the quality of life. As for itstreatment, conventional background therapy still remains effective. La polyarthrite rhumatoïde (PR) est la plus fréquente des maladies auto-immunes. Rarement décrite au Niger, nous rapportons ses aspects épidémiologiques, cliniques, paracliniques, thérapeutiques et évolutifs en milieu hospitalier. Afin d’analyser ces aspects avec plus de détail une étude prospective a été réalisée sur une période d’un (01) an dans le service de rhumatologie du Centre Hospitalier Régional de Maradi. Nous avons inclus tous les cas de PR en accord avec les critères de classifications de l’ACR/EULAR de 2010. Les données ont été saisies et analysées sur le logiciel SPSS 20.0. Après avoir colligé et étudié 32 observations de PR parmi 846 consultations rhumatologiques, les résultats ont démontré des points divers : l’âge moyen des patients était 38,9 ans, le délai diagnostique était de 6 ans et dans quelques cas il y a eu la présence de manifestations extraarticulaires. Les résultats ont également montré que le syndrome inflammatoire était constant et que la prise en charge reste classique avec des moyens non pharmacologiques, des antalgiques, AINS (agent antiinflammatoire non stéroïdien),, infiltrations, et des DMARDs (diseasemodifying anti-rheumatic drug) . L’évolution est favorable dans tous les cas. En bref, la polyarthrite rhumatoïde est une réalité au Niger, de mieux en mieux décrite. Le diagnostic est tardif, les manifestations articulaires et systémiques sont les mêmes que chez les caucasiens mais l’auto-immunité semble moindre. La maladie est très active, altérant la qualité de vie. En ce qui concerne le traitement, le traitement de fond classique reste efficace.